Are horizontal mergers and vertical integration a problem? - Simon Pilsbury; Andrew Meaney (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2009)
This report examines market power in rail markets in Europe arising from horizontal and vertical mergers in the sector, and is intended to provide a high-level basis for discussion at the round table itself. It presents factual information on horizontal and vertical merger cases involving rail freight operators, highlighting the processes used by competition authorities to determine the circumstances in which such mergers should be approved. It also provides commentary on the economics of these markets and, hence, the likely prospects for their future shape. The topic of the report is timely. The first set of results are available from a preparatory study for the European Commission on whether policy objectives with respect to moving freight onto rail can best be achieved by giving freight more priority on the rail network.
Keywords: 330; Eisenbahngüterverkehr; Unternehmensdienstleistung; Horizontale Konzentration; Vertikale Konzentration